Patients with ice hockey injuries presenting to US emergency departments, 1990-2006 - Deits, J.; Yard, E. E.; Collins, C. L.; Fields, S. K.; Comstock, R. D. (Journal of Athletic Training, 2010)
Context: Although the number of US ice hockey participants doubled from 1990 to 2006, no nationally representative studies have examined US ice hockey injuries among participants of all ages during this period.